Xylem Anomalies as Indicators of Maladaptation to Climate in Forest Trees: Implications for Assisted Migration - Sebastian-Azcona, Jaime; Hacke, Uwe; Hamann, Andreas (Frontiers in Plant Science, 2020)
Xylem anomalies that are caused by unusual climate events have long been used to aid cross-dating in tree ring research. Here, we analyzed a range of xylem anomalies in a 39-year-old common garden experiment of white spruce (Picea glauca [Moench] Voss) in central Alberta, Canada, designed to investigate local adaptation. We extracted wood cores from trees representing 24 provenances covering much of the species range across the Canadian boreal forest. Using a double stain and light microscopy analysis, four xylem anomalies and their causes could be distinguished: (1) frost rings indicate issues with synchronizing the onset of growth with the start of the growing season, and were prevalent in young trees; (2) light rings represent thin cell walls caused by an insufficient growing season length, most prevalent in southern sources; (3) blue rings were caused by a failure to complete lignification of new wood due to an early end of the growing season; and (4) double rings represent density fluctuations due to drier than normal summers. Local provenances showed the least amount of xylem anomalies, indicating that they are correctly adapted to the environment in which they occur. In contrast, trees moved to the test site from other climate regions showed various types of xylem anomalies depending on their origin. In particular, populations originating from warmer regions showed an increased presence of latewood anomalies, consistent with a more extensive use of the growing season in the fall. We conclude that xylem anomalies may serve as a sensitive early indicator of maladaptation to climate before populations experience tree dieback or mortality. They may therefore be useful to monitor the health of natural populations, or to evaluate the success of assisted migration in reforestation to address climate change.